1971
DOI: 10.1002/pssb.2220460115
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Short‐Range Order and Long‐Range Order on the Equilibrium Configuration of Superdislocations in FeCo : 2 at% V — Consequences on Flow Stress

Abstract: The variations in flow stress of Fe-Co: 2 atyo V as a function of test or quench temperature exhibit a maximum near the critical temperature for ordering, T,. Transmission microscope study of thin foils reveals the existence of paired dislocations not only at temperatures below T, but also at temperatures above T, where only short-range order exists; calculations of their equilibrium spacing using the quasi-chemical theory [6] are in agreement with experimental results. The peak in flow stress may be explained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1
1

Year Published

1972
1972
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 10 publications
2
27
1
1
Order By: Relevance
“…31, the yield stress exhibits a peak for quench temperatures slightly below the critical temperature (corresponding to S $ 0.4 according to Stoloff and Davies). Identical results have been obtained by Marcinkowski and Chessin [96] and Moine et al [97] (shown in Fig. 31).…”
Section: The Influence Of Order/disordersupporting
confidence: 84%
See 3 more Smart Citations
“…31, the yield stress exhibits a peak for quench temperatures slightly below the critical temperature (corresponding to S $ 0.4 according to Stoloff and Davies). Identical results have been obtained by Marcinkowski and Chessin [96] and Moine et al [97] (shown in Fig. 31).…”
Section: The Influence Of Order/disordersupporting
confidence: 84%
“…Results from Moine et al [97] for strain rates of 3.375 s À1 and 0.0375 s À1 suggest that the position and amplitude of the peak is independent of strain rate. While the difference between the behaviour of FeCo-2V (Fig.…”
Section: The Influence Of Temperaturementioning
confidence: 87%
See 2 more Smart Citations
“…A general agreement is achieved on ODT temperature of stoichiometric FeCo alloy as T o z 1000 K which is the highest of any binary B2-FeCo alloy [3]. The lower ductility and flow stress of ordered B2 phase relative to disordered A2 phase and accompanying anomaly around T o are explained by the transition of slip mechanism from superlattice to single dislocations [4,9,16]. Vanadium alloying is proposed to retard the ODT reaction [6,17] and similarly decrease long range order (LRO) parameter [18,19] relative to pure-FeCo quenched from same temperature.…”
Section: Introductionmentioning
confidence: 65%